PENGARUH VISUAL MERCHANDISING DAN SALES PROMOTION TERHADAP IMPULSE BUYING BEHAVIOUR YANG DI MEDIASI IMPULSE BUYING TENDENCY PADA â€œETUDE HOUSEâ€ GRAND CITY MALL DI SURABAYA - GUNAWAN, OLIVIA (Universitas Katolik Widya Mandala Surabaya, 2013)
This study aims to prove the effect of visual merchandising and sales promotion on impulse buying behavior and impulse buying tendency as mediator variable on Etude House Grand City Mall Surabaya. The sample used is the consumers who live in Surabaya, female age 17-25 years, who knows the South Korean-made cosmetics, and consumers who ever buy cosmetic products in Etude House Grand City Mall Surabaya. The analysis technique used is Stuctural Equation Modeling (SEM), which will make it easier to see the effect of visual merchandising and sales promotion on impulse buying behavior in mediating the impulse buying tendency at Etude House Grand City Mall Surabaya. The results showed that the Visual Merchandising positive effect on Impulse Buying Tendency. Sales promotion has positive influence on Impulse Buying Tendency. Impulse Buying Tendency have positive effect on Impulse Buying Behavior, as well as Visual Merchandising and Sales Promotion indirect effect on Impulse Buying Behavior and Impulse Buying Tendency act as a mediator variable.